2012
DOI: 10.1038/ejhg.2012.133
|View full text |Cite
|
Sign up to set email alerts
|

A newly identified locus for benign adult familial myoclonic epilepsy on chromosome 3q26.32-3q28

Abstract: Benign Adult Familial Myoclonic Epilepsy (BAFME) is an autosomal dominant disorder characterized by adult-onset cortical tremor or action myoclonus predominantly in the upper limbs, and generalized seizures. We investigated a Thai BAFME family. Clinical and electrophysiological studies revealed that 13 were affected with BAFME. There were a total of 24 individuals studied. Genetic analysis by genome-wide linkage study (GWLS) was performed using 400 microsatellite markers and excluded linkage of the previous BA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
67
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(67 citation statements)
references
References 11 publications
0
67
0
Order By: Relevance
“…[5][6][7] In the recent years, a number of loci related to FCMTE at 5p15.31-p15, 3q26.32-3q28 and 10p15, among other sites using subjects in France, Thailand and China, have also been discovered. [8][9][10] In the present study, we selected STR polymorphism markers from the chromosome 5 segments reported at home and abroad, and performed linkage analysis.…”
Section: Discussionmentioning
confidence: 99%
“…[5][6][7] In the recent years, a number of loci related to FCMTE at 5p15.31-p15, 3q26.32-3q28 and 10p15, among other sites using subjects in France, Thailand and China, have also been discovered. [8][9][10] In the present study, we selected STR polymorphism markers from the chromosome 5 segments reported at home and abroad, and performed linkage analysis.…”
Section: Discussionmentioning
confidence: 99%
“…A third disease locus (FAME3) was mapped to chromosome 5p15.31-5p15.1 in a single large French family (Depienne et al 2010), and more recently, a fourth disease locus was reported on chromosome 3q26.32-3q28 (FAME4) in a Thai family (Yeetong et al 2013). In addition to this, a consanguineous Egyptian family with features of FAME has been reported to have a homozygous mutation in the CNTN2 gene on chromosome 1q32 (FAME5) (Stogmann et al 2013).…”
Section: Introductionmentioning
confidence: 93%
“…2a, b, and df). FCMTE studies including several genealogies have presented evidence of a sensorimotor origin for tremulous movements [1,[3][4][5][6][7]. Meanwhile, electromyography (EMG)-fMRI and neurophysiological studies have demonstrated that the tremulous movements in FCMTE patients may be correlated with the activity in the sensorimotor cortex [14,26].…”
Section: Increased Alff In the Frontal Lobementioning
confidence: 99%
“…Four autosomal dominant inherited loci have been reported, including 8q23.3-q24. 13 (Online Mendelian Inheritance in Man, OMIM: 601068), 2p11.1-q12.2 (OMIM: 607876), 5p15.31-p15.1 (OMIM: 613608) and 3q26.32-3q28 [3][4][5][6]. In parallel, one autosomal recessive inherited locus was linked to 1q31.3-32.2 [2].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation